Outcomes associated to the time to treatment with intravenous tenecteplase for acute ischaemic stroke: subgroup analysis of the TRACE-2 randomised controlled clinical trial - Bruce C V Campbell; Yongjun Wang; Yilong Wang; Zixiao Li; Xingquan Zhao; David Wang; Yunyun Xiong; Hao Li; Xia Meng; Yuesong Pan; Lee H Schwamm; Aoming Jin; et al. (Stroke and Vascular Neurology, 2024)
Background The benefit of intravenous alteplase in acute ischaemic stroke (AIS) is time-dependent. Tenecteplase is non-inferior to alteplase among patients with AIS. We aimed to delineate the association of the stroke onset to treatment time (OTT) with tenecteplase compared with alteplase on therapeutic benefit and clinical risks.Methods This is a post hoc analysis of the Tenecteplase Reperfusion therapy in Acute ischaemic Cerebrovascular Events-2 an open-label, randomised, controlled, non-inferior trial. A total of 1430 AIS within 4.5 hours onset at 53 sites in China from 12 June 2021 to 29 May 2022 were randomly assigned (1:1) to receive either tenecteplase 0.25 mg/kg or alteplase 0.9 mg/kg. The primary efficacy outcome was the proportion of participants with a modified Rankin Scale score of 0–1 at 90 days. A post hoc subgroup analysis was conducted with the OTT divided into three intervals (0–90 min, 91–180 min and 181–270 min). The primary safety outcome was symptomatic intracranial haemorrhage within 36 hours post-thrombolytic treatment.Results Treatment was initiated within 270 min of stroke onset in 1412 patients who were randomly allocated to either tenecteplase (n=707) or alteplase (n=705). The OR of primary efficacy outcome was similar as OTT increased (p=0.84). Adjusted odds of an excellent functional outcome were 0.99 (95% CI 0.37 to 2.67) for 0–90 min, 1.23 (95% CI 0.88 to 1.71) for 91–180 min and 1.21 (95% CI 0.88 to 1.65) for 181–270 min. All were in favour of the tenecteplase group. Meta-analysis of 2949 patients yielded a pooled risk difference of 5.54 (95% CI −0.18 to 11.26; p=0.82) in favour of tenecteplase for more than 180 min and 1.77 (95% CI −2.66 to 6.20; p=0.58) for 0–180 min.Conclusions In AIS patients who were treated with either tenecteplase or alteplase within 4.5 hours onset, there was no difference observed in the efficacy and safety between the two groups at the three different OTT time intervals.